Comparison Between Mechanical and Non Mechanical Bowel Preparation Prior To Elective Colorectal Surgery - Altaee, Wissam Jaffar (AL-Kindy College Medical Journal, 2011)
Background: Bowel preparation prior tocolonic surgery usually includes antibiotictherapy together with mechanical bowelpreparation which may cause discomfort to thepatients, prolonged hospitalization and water& electrolyte imbalance.Objective: to assess whether elective colonand rectal surgery may be safely performedwithout preoperative mechanical bowelpreparation.Method: the study includes all patients whohad elective large bowel resection at MedicalCity – Baghdad Teaching Hospital betweenFeb, 2007 to Jan, 2010. Emergency operationswere not included. The patients were randomlyassigned to the 2 study groups (with or withoutmechanical bowel preparation.Results: A total of 165 patients participatedin the study, 82 with mechanical bowelpreparation and 83 without. The 2 groupswere similar in age, sex and type of surgicalprocedure. 134 patients (81.2 %) underwentsurgery owing to colorectal cancer & 31patients (18.8 %) owing to benign disease.The hospitalization period was longer in thebowel-prepared group (mean ± SD, 8.2 ± 5.1days) as compared with the non preparedgroup (mean ± SD, 8.0 ± 2.7 days). However,this difference was not statistically significant.The time until the 1st bowel movement wassimilar between the 2 groups : a mean ± SD of4.2 ± 1.3 days in the non prepared group ascompared with a men ± SD 4.3 ± 1.1 days inthe prepared group ( P = NS ).Conclusion: Our results suggest that noadvantage is gained by preoperativemechanical bowel preparation in electivecolorectal surgery.